Impedance spectroscopy study of dehydrated chitosan and chitosan containing LiClO4 - Costa, M. M.; Terezo, A. J.; Matos, A. L.; Moura, W. A.; Giacometti, Jose A. [UNESP]; Sombra, A. S. B. (Elsevier B.V., 2010)
Cast films of chitosan and chitosan containing LiClO4 were characterized using Fourier transform infrared spectroscopy and the thermogravimetric technique. The electric properties of hydrated and dehydrated films were investigated with impedance spectroscopy in the frequency range from 0.1 Hz to 1 MHz, at temperatures varying from 30 to 110 degrees C. The frequency dependence of the impedance for dehydrated chitosan and chitosan containing LiClO4 films indicated ionic conduction. Two relaxation peaks were evident on the imaginary curve of the electric modulus, which were assigned to ionic conduction. The peak at higher frequency was found for chitosan and chitosan containing LiClO4 films. The peak at lower frequency was attributed to Li+ conduction since it appeared only for the chitosan containing LiClO4. The peak frequency varied with the temperature according to an Arrhenius process with activation energies of circa of 0.6 and 0.45 eV, for H+ and Li+ conduction, respectively. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Chitosan; Polymer films; Electric properties; Electric modulus